ANALISIS ASUHAN KEPERAWATAN KELUARGA PADA LANSIA DENGAN ASAM URAT MELALUI INTERVENSI INOVASI SENAM ERGONOMIS UNTUK MENURUNKAN KADAR ASAM URAT DI RT 06 RW 07 KELURAHAN GROGOL KOTA DEPOK - Afifah Afriana (2023)
The elderly are prone to health problems in the musculoskeletal system. One of the joint disorders that is often experienced by the elderly is gout. One of the non-pharmacological therapies that can be done by the elderly is ergonomic exercise. Ergonomic gymnastics is a gymnastic technique that has the goal of restoring position and increasing the flexibility of the nervous system to maximize oxygen to the brain, the body's combustion system and to help expedite the body's metabolism. The implementation of ergonomic exercises in managed patients and resume patients was carried out in 6 meetings for 2 weeks. The results of the application of ergonomic exercises showed a decrease in the average uric acid level in elderly patients being managed from 8.5 mg/dl to 6.0 mg/dl. Whereas on resume clients the average value of decreasing uric acid levels shows results from 6.80 mg/dl to 6.45 mg/dl. These results indicate that ergonomic exercises are effective for the elderly, both managed and resume clients, to reduce uric acid levels in the body. Community nurses are expected to be able to apply ergonomic exercises as a non-pharmacological therapy for clients with gout